PanStop: a decade of rapid containment exercises for pandemic preparedness in the WHO Western Pacific Region - Moturi, Edna Kwamboka; Horton, Katherine; Bell, Leila; Breakwell, Lucy; Dueger, Erica (Western Pacific Surveillance and Response, 2018)
Member States in the Western Pacific Region (WPR) of the World Health Organization (WHO), are highly vulnerable to emerging influenza viruses that have the potential to cause global pandemics. A well-coordinated strategy for preparedness is required at national and international levels for a robust response and to mitigate the potentially dire consequences of the next influenza pandemic. Of 37 countries and areas in the region, 23 have publically available national pandemic influenza preparedness and response plans; of these, only 17% have been updated in the last five years. However, many plans are pending update and may benefit from integrating some components of the 2017 WHO pandemic influenza risk management guide. Additionally, many plans need to be operationalized to test their functionality. Since 2007, WPRO has conducted annual PanStop exercises to test pandemic containment plans and RC mechanisms in a simulated environment that imitates pandemic events as they unfold. PanStop exercises provide an opportunity for countries to validate policies, protocols and procedures involved in implementing rapid containment (RC) operations, and to identify strengths and opportunities for improvement in planning activities for pandemic influenza. By participating in exercises such as PanStop and the annual regional International Health Regulation (IHR) Crystal Exercise, and subsequently adapting national preparedness plans based on exercise outcomes, WPR continues to improve readiness for the next influenza pandemic.